Microclimate Characteristics in Mangrove Forest Areas in Padang City - Aditio, Rama; Yendri Sudiar, Nofi; Dwiridal, Letmi; Amir, Harman (Journal of Climate Change Society, 2023)
Mangrove forest microclimate is the climatic conditions that occur in mangrove forests. The research aims to determine the conditions and characteristics of the microclimate (air temperature, air humidity and light intensity) in the mangrove forest area. The research location was chosen in the Taluak Buo mangrove forest area because the conditions and characteristics of the microclimate are not yet known. The data used is prime data obtained from direct measurements in the field. Measurements of several weather elements were carried out three times, namely in the morning (07.00-08.00 WIB), in the noon (12.00-13.00 WIB), and in the afternoon (17.00-18.00 WIB) for 7 days at three observation points using an anemometer instrument. The results obtained from this research in the Taluak Buo mangrove forest area in the Bungus Teluk Kabung sub-district are an average daily air temperature of 26.94°C in the forest, 27.94°C at the position on the edge of the forest and 28.6°C at outside the forest. The average difference in air temperature between inside the forest and outside the forest is between 1,22-2,14°C. On the other hand, the difference in air humidity is 5-6%. The average difference in sunlight intensity between inside the forest and outside the forest is between 3.923,44-22,462,66 lux. The air temperature and intensity of sunlight inside the forest is lower than at the edge and outside the forest, which is inversely proportional to the higher air humidity inside the forest.